NATIONAL WEBINAR: COMPILATION OF CLASS ACTION RESEARCH AND POPULAR SCIENTIFIC WORKS FOR PAI TEACHER - Sari, Mayang; Junaidah, Junaidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research activity aims to improve the ability and skills of a teacher in compiling and implementing Classroom Action Research (PTK) and Popular Scientific Work. Participants in this national webinar activity came from PAI teachers throughout Indonesia. This webinar activity was held in three stages: the first stage began with the opening of the webinar event as well as the presentation of material on the basic concepts of PTK, the second stage continued with the concept of Popular Scientific Work, and in the third stage this was assistance with the draft PTK proposal. This webinar activity has been running in accordance with the event schedule and can make a positive contribution to all PAI teachers throughout Indonesia regarding the preparation of PTK proposals and Popular Scientific Works. Apart from that, this webinar activity can increase teachers' knowledge and insight into what are the basic thoughts that must be conceptualized in the background of PTK research, but there are a few points of thought that have not been developed into detailed paragraphs and tips and tricks for writing Popular Scientific Works. With great hope after this national webinar activity, PAI teachers can explore the competencies they already have.